Controle baseado em preditor com atenuação de perturbação para sistemas de tempo discreto com atraso na entrada - Machado, Gabriel Freitas (2022)
In this work, a predictor-based control structure is proposed for discrete-time systems with input delay. This strategy allows to completely attenuate disturbances of known dynamics in steady state from the output of the system. For this, an augmented state observer is used in which the controller dynamics is considered and a predictor based on this observer is used to estimate the state of the discrete-time system. The predictor-based feedback matrix and the augmented state observer gain matrix are calculated using a synthesis procedure. Some of the results recently proposed in the literature for predictor-based controllers are presented in a systematic way in the text, where the approaches are extended to the case in which there is no access to the system state and to the synthesis problem based on a result of the literature. The proposed control structure is compared to the presented techniques and has, in general, superior performance.